The Role of Social Support on Resilience in People Living With HIV/AIDS : A Systematic Literature Review - Firman Firman; Sri Yona; Allenidekania Allenidekania (Universitas Muhammadiyah Surabaya, 2022)
During the COVID-19 pandemic, it had a fairly heavy psychological impact, so resilience or resilience was needed, especially for people with HIV/AIDS (PLWHA). This study is to determine the role of social support on resilience in people with HIV/AIDS. Resilience is a person's ability to adapt, survive and thrive in difficult situations. This study used a systematic literature review, which was carried out by means of a systematic review of several articles discussing social support and resilience in people with HIV/AIDS. Article criteria include international publication in English and full text. Article searches were carried out in February 2022 through 4 databases, namely PubMed, Wiley, Proquest, and Springer. Search using keyword (